난소 절제 여성의 영양소 섭취 상태가 골밀도 및 골무기질 함량에 미치는 영향 - 최미자(Choi Mi-Ja) (Hanʼguk yongyang hakhoe chi, 2003)
This study investigated associations between nutrient intake, lumbar bone mineral density (BMD) , and bone mineral content (BMC) among 33 ovariectomized women (mean age =47.2 y) . Forty-five premenopausal women participated as a control group. The BMD and BMC of the lumbar spine (L$_2$-L$_4$) were measured by dual energy x-ray absorptiometry. Nutrient intake was estimated by the convenient method and a quantitative food frequency questionnaire was designed for this study that included the most commonly consumed foods sources of calcium. Participants were asked to identify all daily physical activities, and the number of hours per activity. The participants were also grouped by calcium intake. The total calcium intake of all participants was estimated by dietary calcium intake and then the subjects were divided into quartiles to assess the lumbar BMD and BMC of the highest quartile and the lowest quartile of calcium intake. The ovariectomized women consumed 602 mg/d of calcium which is 86% of RDA. There were significant differences in lumbar BMD and BMC between control and ovariectomized group. Within ovariectomized group the highest quartile calcium intake group had significantly greater lumbar bone mineral density and bone mineral content than the lowest quartile calcium intake group. Correlation analysis revealed that the ALP was positively associated with calcium index in control women, while ALP was positively associated with energy intake in ovariectomized women. And body weight was positively correlated with the spinal BMD and BMC in all women. The spinal BMD was negatively associated with menarche age, number of child, and the age of last child delivery, and age in control women. However, neither menarche age nor the age of last child delivery were associated with both spinal BMD in ovariectomized women. These results confirmed that ovariectomized and low calcium intake is associated with poor bone mineral density. Energy and calcium intake and adequate body weight should be recommended in ovariectomized women to prevent osteoporosis.